Limiting the application scope of the doctrine of vicarious liability in deviation cases within labour law context: comparative appraisal - Shiringane, Philemon (My University, 2024)
The employment contract comes with both benefits and liabilities for both employers and employees. For example, employers in South Africa often suffer from financial liability when their employees commit misconduct that causes damages to third parties. This occurs with the application of the principle of vicarious liability. This principle holds employers liable for the misconduct of their employees. The purpose of this study is to critically analyse the scope of application of the principle of vicarious liability in deviation cases while considering its reasonableness and the financial damages employers suffer due to it in South Africa. The study made use of the desktop method of data collection to find primary sources and secondary sources of law. The study analysed the case of Stallion Security (Pty) Ltd v Van Staden [2019] whereby the scope of the principle of vicarious liability was extended by the Supreme Court of Appeal (SCA) to also hold employers liable for conduct committed by off-duty employees. The SCA in this case reasoned that as long as employment duties granted an off-duty employee an advantage to commit misconduct, an employer should be liable. A point of concern from this precedent is the implications it has on the liability of employers in the sense that employers in South Africa will have to defend against claims brought in terms of the doctrine of vicarious liability. The study considered fairness to be important and after comparative analysis, found that the United Kingdom courts apply the principle of vicarious liability with fairness and reasonableness such that employers are still afforded some protection. It was recommended that courts in South Africa should learn from UK law to limit the scope of application of the principle of vicarious liability. In addition to this, employers should also rely on liabilities such as piercing of corporate veil and liability for breaching a fiduciary duty to make employees such as directors and senior executives liable for their misconduct.
Thesis (LLM. (Labour law)) -- University of Limpopo, 2024
Keywords: Vicarious labiality; Deviation cases; Wider scope; South Africa; United Kingdom; Limiting the scope of application; Misconduct in office -- Law and legislation; Liability (Law) -- South Africa; Labor laws and legislation -- South Africa; Respondeat superior